ANALISIS HIRA (HAZARD IDENTIFICATION AND RISK ASSESSMENT) PADA INSTANSI X DI SEMARANG - Prasetyo, Erwan Henri; Suroto, Suroto; Kurniawan, Bina (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Hazard identification is a step in the discovery of potential loss or accident. One of the instruments in hazard identification is HIRA which contains potential hazards, risks, controls and risk assessments. Institute X is one that have potential fire hazard from electrical installation. The purpose of this research is to analyze HIRA (Hazard Identification and Risk Assessment) at Institute X in Semarang. This research is a descriptive research with observation method. Observations made in this study focused on observing the hazards of electrical installations, fire risks, light extinguishers and evacuation routes. The results of this study indicate that electrical installation hazards consist of peeled cables and improper plugs. Risks that can be caused, among others, short circuit, electric shock and fire. The existing fire risk is injury and damage to facilities and infrastructure in Institute X. Light extinguishers are available installed with a buffer and some are placed in the APAR cupboard in unlocked condition. But still found 3 APAR in empty condition, 3 APAR under pressure decreases condition. The evacuation route is available but still found some unsafe conditions that hinder emergency evacuation. Thus, Institute X still has the potential for fire coming from electrical hazards. In order for Institute X to minimize the potential fire hazard, it is necessary to control the electrical hazard by isolating the open cable, giving the cover to the power source to avoid the konsletin and the risk of electric shock and to do the maintenance of the fire control facilities.